3D organoid cultivation improves the maturation and functional differentiation of cholangiocytes from human pluripotent stem cells - Budi, Nova Yuli Prasetyo; Lai, Wei-Yu; Huang, Yen-Hua; Ho, Hong-Nerng (Frontiers in Cell and Developmental Biology, 2024)
Idiopathic cholangiopathies are diseases that affect cholangiocytes, and they have unknown etiologies. Currently, orthotopic liver transplantation is the only treatment available for end-stage liver disease. Limited access to the bile duct makes it difficult to model cholangiocyte diseases. In this study, by mimicking the embryonic development of cholangiocytes and using a robust, feeder- and serum-free protocol, we first demonstrate the generation of unique functional 3D organoids consisting of small and large cholangiocytes derived from human pluripotent stem cells (PSCs), as opposed to traditional 2D culture systems. At day 28 of differentiation, the human PSC–derived cholangiocytes expressed markers of mature cholangiocytes, such as CK7, CK19, and cystic fibrosis transmembrane conductance regulator (CFTR). Compared with the 2D culture system–generated cholangiocytes, the 3D cholangiocyte organoids (COs) showed higher expression of the region-specific markers of intrahepatic cholangiocytes YAP1 and JAG1 and extrahepatic cholangiocytes AQP1 and MUC1. Furthermore, the COs had small-large tube-like structures and functional assays revealed that they exhibited characteristics of mature cholangiocytes, such as multidrug resistance protein 1 transporter function and CFTR channel activity. In addition to the extracellular matrix supports, the epidermal growth factor receptor (EGFR)-mediated signaling regulation might be involved in this cholangiocyte maturation and differentiation. These results indicated the successful generation of intrahepatic and extrahepatic cholangiocytes by using our 3D organoid protocol. The results highlight the advantages of our 3D culture system over the 2D culture system in promoting the functional differentiation and maturation of cholangiocytes. In summary, in advance of the previous works, our study provides a possible concept of small-large cholangiocyte transdifferentiation of human PSCs under cost-effective 3D culture conditions. The study findings have implications for the development of effective cell-based therapy using COs for patients with cholangiopathies.